Carnarvon Gorge: safekeeping a place and Indigenous agency within rock art research and management. Issue 2 (4th May 2019) - Giorgi, Marisa; Taçon, Paul S. C.
Abstract: One of the aspects that distinguishes the investigation and conservation of rock art in Australia, the Americas and parts of Africa from other parts of the world is the intrinsic link between rock art and living Indigenous cultures. Many Australian rock art sites benefit from the presence of a continuity of cultural connectedness. There are both challenges and advantages to these connections in relation to rock art research and site management. We discuss these by focussing on two sites located in Carnarvon Gorge in the remote Southern Central Highlands of Queensland. These sites, Art Gallery and Cathedral Cave, manifest cultural continuity, albeit with some disruptions. We show how Indigenous knowledge frameworks can be incorporated into rock art research and site management, especially for the prevention of site vandalism such as graffiti. There is a need to translate this into more robust policy design that brings Indigenous involvement to the fore. As has been argued for a number of Australian and international rock art sites, the incorporation of the Indigenous voice in site management enhances the safeguarding of the rock art for current and future generations. However, there are many challenges for Indigenous communities wanting to be more directly involved in the management of their heritage including Carnarvon Gorge, Queensland.